2018
DOI: 10.1111/joic.12523
|View full text |Cite
|
Sign up to set email alerts
|

The effects of types of guidewires and pressure applied during stent implantation in the main vessel on the incidence of damage to coronary guidewires during angioplasty of coronary bifurcation lesions—Wide Beast study

Abstract: The inflation pressure during stent implantation had no impact on "jailed" guidewire damage. The difference in the prevalence of serious damage and total damage number was statistically significant for the BMW guidewire compared to the Pilot50. The BMW guidewire was an independent predictor of the degree of damage to the guidewire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The ability to create a loop shape differs among types of guidewires. Experimental studies of loop shape have been reported in endourology and the endovascular field [12][13][14][15], but not in the pancreatic and biliary endoscopic fields [15]. In addition, from the perspective of loop shape, no evidence has been accumulated regarding which guidewires most easily take on a loop shape.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to create a loop shape differs among types of guidewires. Experimental studies of loop shape have been reported in endourology and the endovascular field [12][13][14][15], but not in the pancreatic and biliary endoscopic fields [15]. In addition, from the perspective of loop shape, no evidence has been accumulated regarding which guidewires most easily take on a loop shape.…”
Section: Introductionmentioning
confidence: 99%